2012
DOI: 10.1039/c2cc37337h
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl isomerism in amorphous Mn(TPP)(NO) solids

Abstract: Reaction of NO with amorphous Mn(TPP) layers gives two Mn(TPP)(NO) isomers with linear and bent Mn-N-O geometries that reversibly interconvert with changes in temperature. DFT computations predict that the linear complex is the singlet ground state while the bent structure is a triplet state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
5
22
0
Order By: Relevance
“…Such an increase of the MLCT has already been found in stationaryc alculations of other nitrosyl complexes. [28,36,37] The angle of 1428 reached during this time is consistentw ith the optimized Ru-N-O bending angle of the 3 GS isomer,d ef acto the nearest reachable minimum along the N!Oi somerization pathway (see Ta ble S7 and Figure S7 in the SupportingInformation). Concomitantt othe Ru-N-O bending, the RuÀNO distance elongates, increasing from approximately 1.76 A( the value of the 1 GS isomer) to approximately 2.20 during the first 60 fs.…”
Section: Dynamical Studiessupporting
confidence: 74%
“…Such an increase of the MLCT has already been found in stationaryc alculations of other nitrosyl complexes. [28,36,37] The angle of 1428 reached during this time is consistentw ith the optimized Ru-N-O bending angle of the 3 GS isomer,d ef acto the nearest reachable minimum along the N!Oi somerization pathway (see Ta ble S7 and Figure S7 in the SupportingInformation). Concomitantt othe Ru-N-O bending, the RuÀNO distance elongates, increasing from approximately 1.76 A( the value of the 1 GS isomer) to approximately 2.20 during the first 60 fs.…”
Section: Dynamical Studiessupporting
confidence: 74%
“…(Note that the triplet isomer is slightly overstabilized by the B3LYP* functional which was used for energy curves in Figure 4; according to the experimental data, Mn(TPP)(NO) is the singlet ground state, 22 the triplet lying ∼1 kcal/mol above. 55 ) Although the triplet isomer is already associated and its formation should be fast, i.e., there is no barrier on crossing from the (S = 2) to (S = 1) curve in Figure 4b, the experimental kinetic data of NO recombination more probably reflect the rate of formation of the singlet ground state. 75 As seen in Figure 4b, when going from the triplet (intermediate) to singlet isomer (final product), there is an energy barrier to surpass.…”
Section: Inorganic Chemistrymentioning
confidence: 97%
“…21 Recently, Kurtikyan et al suggested that the complex kinetic behavior observed by Kubiak et al may be due to the existence of a relatively stable triplet isomer of Mn(TPP)(NO), which they discovered in amorphous solid phase. 55 The equilibrium geometry of this triplet state has a bent MnNO motif and corresponds to the deep minimum on the (S = 1) curve in Figure 4b. (Note that the triplet isomer is slightly overstabilized by the B3LYP* functional which was used for energy curves in Figure 4; according to the experimental data, Mn(TPP)(NO) is the singlet ground state, 22 the triplet lying ∼1 kcal/mol above.…”
Section: Inorganic Chemistrymentioning
confidence: 98%
“…Although Mulliken population analysis is known to be basis set dependent and should be used with caution, these qualitative results are indicative that the electronic coupling between NO and the metal center can explain the linear NO coordination mode to Ru 3 O, even if NO is still regarded as a formal zero charge ligand. Indeed, Ford and co-workers have recently shown that NO can coexist as linear and bent coordination isomers depending on the spin state of a MnII(NO)porphyrinate complex [36]. They have found that singlet ground state is linearly coordinated but for another very close triplet state NO is bent with essentially the same configuration for Mn(II), i.e., the formal oxidation states of the metal center and NO are not changed.…”
Section: Electronic Spectroscopy Molecular Modeling and Electrochemimentioning
confidence: 98%